Radioimmunoassay kits for thyroid hormones. Issue 10 (October 1976) - Jackson, P; Lees, S; Pow, M; Willing, G W; Watson, D
Abstract : Characteristics of the T4 and T3 radioimmunoassay kits that are commercially available in the UK are described. Useful comparative data and criticism are given about many of these kits. Some unacceptable variation in accuracy is demonstrated.